2021
DOI: 10.1186/s40246-021-00353-0
|View full text |Cite
|
Sign up to set email alerts
|

Perception of personalized medicine, pharmacogenomics, and genetic testing among undergraduates in Hong Kong

Abstract: Background The global development and advancement of genomic medicine in the recent decade has accelerated the implementation of personalized medicine (PM) and pharmacogenomics (PGx) into clinical practice, while catalyzing the emergence of genetic testing (GT) with relevant ethical, legal, and social implications (ELSI). Results The perception of university undergraduates with regards to PM and PGx was investigated, and 80% of undergraduates value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 76 publications
2
9
0
Order By: Relevance
“…Malay students were shown to be extremely worried about it along with the existence of phenomena of racial and religious discrimination and privacy deprivation. Cheung et al [ 32 ] stated that the majority of undergraduate students believed that the biggest threats of genetic testing, implementation were “Patient Privacy” (80%) and “Data Confidentiality” (68%), supporting our findings. In general, many studies have pointed out similar conclusions especially in terms of religiosity and religious restrictions [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 87%
“…Malay students were shown to be extremely worried about it along with the existence of phenomena of racial and religious discrimination and privacy deprivation. Cheung et al [ 32 ] stated that the majority of undergraduate students believed that the biggest threats of genetic testing, implementation were “Patient Privacy” (80%) and “Data Confidentiality” (68%), supporting our findings. In general, many studies have pointed out similar conclusions especially in terms of religiosity and religious restrictions [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 87%
“…Most of them never received personal genetic sequencing. The result was consistent with a recent survey conducted in Hong Kong that undergraduates showed a high awareness of PM but insufficient genetic-related knowledge [23].…”
Section: Plos Onesupporting
confidence: 92%
“…In order to enhance understanding and mitigate genetic discrimination, unprecedented global coalition is of paramount importance to improve inclusivity of the RD population. Previous studies have demonstrated participants' concerns on genetic discrimination in the context of employment and insurance ( 140 142 ). In particular, undergraduates in Hong Kong were found to be pessimistic toward unfavorable genetic testing results, with almost 60% of the respondents claiming that they would feel “inadequate or different,” 56% would feel helpless, and nearly 60% perceived that they would be disadvantaged in job seeking in case of unfavorable genetic testing results ( 140 ).…”
Section: Future Directions Of Rdsmentioning
confidence: 99%
“…Previous studies have demonstrated participants' concerns on genetic discrimination in the context of employment and insurance ( 140 142 ). In particular, undergraduates in Hong Kong were found to be pessimistic toward unfavorable genetic testing results, with almost 60% of the respondents claiming that they would feel “inadequate or different,” 56% would feel helpless, and nearly 60% perceived that they would be disadvantaged in job seeking in case of unfavorable genetic testing results ( 140 ). It is of utmost importance to eliminate the root causes of stigmatization and discrimination of the RD population in order to improve social inclusion and reduce opportunities and productivity loss.…”
Section: Future Directions Of Rdsmentioning
confidence: 99%